PENGADAAN BUKU BACAAN UNTUK MENUNJANG KEGIATAN LITERASI DI SMP ISLAM AL-MA’ARIF 02 SINGOSARI - Setyowati, Lestari -; Karmina, Sari -; Zubaidi, Nanang - (Faculty of Cultural Studies, Universitas Brawijaya, 2023)
The community service activity was aimed at procuring reading books to support literacy activities at Al-Ma’arif Islamic Middle School 02 Singosari. The methods used in this activity were 1) conducting an initial study to determine the problems and needs of the school’s reading books, 2) making program plans, 3) coordinating with the school, 4) having internal coordination with the team, 5) implementing the program, 6) reflecting activity. The result of the community service activities was as follows. The problems found was that the students lack interest in reading. One reason was the lack of variety of reading books in the library. The procurement of books at AlMaarif Islamic Middle School was carried out through raising donations (7%) and purchasing books (93%). The books donated to the school were in various genres, including educational, motivational, historical, fairy tales, novels, short story anthologies, comics on knowledge, and popular comics. The reflection results show that students like the variety of books donated to school, and there was a desire for the school to create a literacy corner and literacy activities in the coming semester.